Comparative analysis on application of pass technique of tossers in China and foreign countries in matches in fast ball cover - Zhang, K.-L.; Gao, H.; Zhang, L.; Gao, P.-H.; Shi, F. (AIP Conference Proceedings, 2020)
In this study, based on physiology and sports biology, by using the methods of literature review and video analysis, we compared the distribution data of the tosser in the 2018 world series of excellent Chinese and foreign women volleyball matches, to explore the shortcomings of the Chinese women volleyball tossers in organizing attacks. The study shows that there are great differences in pass speed, pass timing and passing choice of tosser between Chinese women volleyball team and foreign excellent teams. In the organization of tactical attack, the timing of the tosser is too early compared with the timing of the cover jump of the second spiker, and the blocking players of the other team do not take off without swaying, resulting in the general cover effect. The passing to Position 2 and 4 has a low start point, slow speed and high radian, and the opposing blocking players can still keep up with the passing speed and move to the appropriate position to participate in the effective blocking after being cheated and taken off. After the opponents block player is cheated, the tosser does not quickly pass the ball to the weak block striker, causing the delayed opportunity. If the rhythm of the tosser is not changeable, it is easy for the opponent to organize block effectively.